Granulocyte colony-stimulating factor does not promote neurogenesis after experimental intracerebral haemorrhage - Kallmünzer, Bernd; Tauchi, Miyuki; Schlachetzki, Johannes; Machold, Kristin; Schmidt, Ariana; Winkler, Jürgen; Schwab, Stefan; Kollmar, Rainer (International Journal of Stroke, 2014)
Hematopoietic growth factors have been suggested to induce neuroprotective and regenerative effects in various animal models of cerebral injury. However, the pathways involved remain widely unexplored.This study aimed to investigate effects of local and systemic administration of granulocyte colony-stimulating factor on brain damage, functional recovery, and cerebral neurogenesis in an intracerebral haemorrhage whole blood injection model in rats.Eight-week-old male Wistar rats (n = 100) underwent induction of striatal intracerebral haemorrhage by autologous whole blood injection or sham procedure and were randomly assigned to either (a) systemic treatment with granulocyte colony-stimulating factor (60 ?g/kg) for five-days; (b) single intracerebral injection of granulocyte colony-stimulating factor (60 ?g/kg) into the cavity; or (c) application of vehicle for five-days. Bromodeoxyuridine-labelling and immunohistochemistry were used to analyze proliferation and survival of newly born cells in the sub-ventricular zone and the hippocampal dentate gyrus. Moreover, functional deficits and lesion volume were assessed until day 42 after intracerebral haemorrhage.Differences in lesion size or hemispheric atrophy between granulocyte colony-stimulating factor-treated and control groups did not reach statistical significance. Neither systemic, nor local granulocyte colony-stimulating factor administration induced neurogenesis within the dentate gyrus or the sub-ventricular zone. The survival of newborn cells in these regions was prevented by intracerebral granulocyte colony-stimulating factor application. A subtle benefit in functional recovery at day 14 after intracerebral haemorrhage induction was observed after granulocyte colony-stimulating factor treatment.There was a lack of neuroprotective or neuroregenerative effects of granulocyte colony-stimulating factor in the present rodent model of intracerebral haemorrhage. Conflicting results from functional outcome assessment require further research.
EVALuna2:22279

Ischemic stroke associated with the use of a synthetic cannabinoid (spice) - Möller, Sebastian; Luecke, Caroline; Struffert, Tobias; Schwarze, Bernhard; Gerner, Stefan; Schwab, Stefan; Köhrmann, Martin; Machold, Kristin; Philipsen, Alexandra; Mueller, Helge H. (Asian Journal of Psychiatry, 2017)
Synthetic cannabinoids, i.e. "spice", are psychoactive drugs with increasing use worldwide. Spice may have harmful neuropsychiatric and physical side effects. Here, we present the case of a 25-year-old man with ischemic stroke after smoking spice on the previous evening. Diagnostic work-up was negative for other common causes of stroke. Toxicology screen unveiled the cannabimimetic ADB-FUBINACA in the drug sample and in patient's urine. The cardiac sympathomimetic effect of spice might have triggered an unnoticed episode of tachyarrhythmia and resulted in stroke via cardioembolic etiology. Thus, in absence of other risk factors, a careful patient history of spice use is recommended for patients with acute neurological deficits.
EVALuna2:22545